Changes in the expression of NO synthase isoforms after ozone: the effects of allergen exposure - Jang, An-Soo (BioMed Central, 2004)
BACKGROUND: The functional role of nitric oxide (NO) and various nitric oxide synthase (NOS) isoforms in asthma remains unclear. OBJECTIVE: This study investigated the effects of ozone and ovalbumin (OVA) exposure on NOS isoforms. METHODS: The expression of inducible NOS (iNOS), neuronal NOS (nNOS), and endothelial NOS (eNOS) in lung tissue was measured. Enhanced pause (P(enh)) was measured as a marker of airway obstruction. Nitrate and nitrite in bronchoalveolar lavage (BAL) fluid were measured using a modified Griess reaction. RESULTS: The nitrate concentration in BAL fluid from the OVA-sensitized/ozone-exposed/OVA-challenged group was greater than that of the OVA-sensitized/saline-challenged group. Methacholine-induced P(enh )was increased in the OVA-sensitized/ozone-exposed/OVA-challenged group, with a shift in the dose-response curve to the left, compared with the OVA-sensitized/saline-challenged group. The levels of nNOS and eNOS were increased significantly in the OVA-sensitized/ozone-exposed/OVA-challenged group and the iNOS levels were reduced compared with the OVA-sensitized/saline-challenged group. CONCLUSION: In mice, ozone is associated with increases in lung eNOS and nNOS, and decreases in iNOS. None of these enzymes are further affected by allergens, suggesting that the NOS isoforms play different roles in airway inflammation after ozone exposure.